Flood estimation at ungauged catchments of western catchments of Karnataka, West coast of India. Issue 3 (2nd September 2019) - Reddy, N. Amaranatha; Seelam, Jaya Kumar; Rao, Subba; Nagaraj, M. K.
Abstract: Many catchments in India are devoid of gauging stations. In the absence of measurements of stream flow, regional rainfall-runoff relationships developed over a hydro-meteorologically similar region may be used to estimate flood discharge at ungauged catchments. This study includes testing of different methods wherein a representative basin could be used to develop a Synthetic Unit Hydrograph (SUH) within its hydro-meteorological similar region. Derivation of SUH using Central Water Commission (CWC) flood estimation was tested on 13 catchments for Konkan and Malabar coasts on the west coast of India. The five methods are (i) CWC Dimensionless approach, (ii) Snyder method, (iii) SCS method, (iv) Two Parameter Gamma Distribution method and (v) Hybrid model. Inter-comparison of the SUHs and unit hydrographs derived from precipitation data is carried out. Amongst all methods tested the Two parameter Gamma Distribution method and Hybrid model satisfies the Unit Hydrograph criterion whereas, traditional methods of Snyder, SCS, CWC-SUH and CWC dimensionless methods require manual adjustments of the characteristics points and have a significant degree of subjectivity and trial and error. The above-said methods including CWC method are used to estimate flood discharge at ungauged catchments of the coastal districts along Karnataka coastline.